Effect of Soorh Metakaolin on Concrete Compressive Strength and Durability - Saand, A.; Keerio, M. A.; Bangwar, D. K. (Engineering, Technology & Applied Science Research, 2017)
Concrete durability is a key aspect for forecasting the expected life time of concrete structures. In this paper, the effect of compressive strength and durability of concrete containing metakaolin developed from a local natural material (Soorh of Thatta Distict of Sindh, Pakistan) is investigated. Soorh is calcined by an electric furnace at 8000C for 2 hours to produce metakaolin. One mix of ordinary concrete and five mixes of metakaolin concrete were prepared, where cement is replaced by developed metakaolin from 5% to 25% by weight, with 5% increment step. The concrete durability was tested for water penetration, carbonation depth and corrosion resistance. The obtained outcomes demonstrated that, 15% replacement level of local developed metakaolin presents considerable improvements in concrete properties. Moreover, a considerable linear relationship was established between compressive strength and concrete durability indicators like water penetration, carbonation depth and corrosion resistance.